1983
DOI: 10.1037/0022-006x.51.4.565
|View full text |Cite
|
Sign up to set email alerts
|

Emotional, behavioral, and physiological effects of chronic stress at Three Mile Island.

Abstract: The present study evaluated the psychophysiological impact of a powerful environmental stressor-the uncertainty and threat during the aftermath of the nuclear accident at Three Mile Island (TMI). TMI residents were compared with samples of people living near an undamaged nuclear power plant, people living near a traditional coal-fired power plant, and people living in an area more than 20 miles from any power plant. A number of self-report measures of psychological stress were evaluated by administering the Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
2
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(154 citation statements)
references
References 14 publications
7
143
2
2
Order By: Relevance
“…These accounts may be affected by the shocking experience and the impacts suffered and may therefore be not entirely reliable. However, literature suggests that a good recall of disaster experiences is actually possible, even over long periods of time (Baum et al 1983, Verger et al 2003. In our study, the consistence of results with other biophysical reports and the congruence between the magnitude of transformations and the impacts on levels of well-being in different geographical sectors, suggests the validity of respondents' recall.…”
Section: Discussionsupporting
confidence: 56%
“…These accounts may be affected by the shocking experience and the impacts suffered and may therefore be not entirely reliable. However, literature suggests that a good recall of disaster experiences is actually possible, even over long periods of time (Baum et al 1983, Verger et al 2003. In our study, the consistence of results with other biophysical reports and the congruence between the magnitude of transformations and the impacts on levels of well-being in different geographical sectors, suggests the validity of respondents' recall.…”
Section: Discussionsupporting
confidence: 56%
“…Conclusions of the above studies showed how distance affects residents' attitude towards the NIMBY facilities. Several studies showed that people who lived near the nuclear power plant of Three Mile Island had stronger stress reactions than people who lived far away [53,54]. Huppe and Weber [52] found an inverted U-shaped relationship between the strength of opposition towards nuclear power plants and the distance of dwelling place to the plant.…”
Section: Methods Of Testing the Nimby Syndromementioning
confidence: 99%
“…There are four principal methodological problems. First, the same experience may be apprehended very differently from one individual to another as a function, in particular, of his or her coping style; in addition, individual reports can depend on the person's psychological and emotional state at the moment they are questioned (Baum et al, 1983); these questions raise the problems of reproducibility and reliability of the information collected. Second, to establish a causal link between the postdisaster PD and a disaster-related experience, ''exposureeffect'' relations must be tested and thus the intensity and severity of cumulative exposure to disaster stressors must be quantified.…”
Section: Introductionmentioning
confidence: 99%